Seasonal and Spatial Variation of Pelagic Microbial Food Web Structure in a Semi-Enclosed Temperate Bay - Li, Haibo; Chen, Xue; Denis, Michel; Zhao, Yuan; Huang, Lingfeng; Jiang, Zengjie; Zhang, Wuchang; Xiao, Tian (Frontiers in Marine Science, 2020)
Microbial food web (MFW) in the seawater encompasses the smallest organisms: viruses, autotrophic prokaryotes and heterotrophic prokaryotes (HP), nanoflagellates, eukaryotic phytoplankton and ciliates. For many years, scientists investigated the MFW structure differences in distinct water masses. However, the MFW structure seasonal variation in coastal areas remains poorly documented. In this study, we report on the seasonal and spatial variations of the MFW structure in the temperate Sanggou Bay in four successive seasons, from spring to winter. With a temperature increase from 1.90 to 24.20C, HP biomass increased from 3.77 to 135.77 μg C dm-3, almost covering the whole variation range for the global ocean. The autotrophic (AUTO) components, including Synechococcus (SYN), phototrophic picoeukaryotes (PEUK) and pigmented nanoflagellates (PNF), exhibited biomass variation ranges as large as previously reported. The MFW structure seasonal variation was driven by MFW relative biomasses (biomass ratios of MFW components to HP). With the increase of HP biomass, PNF and PEUK relative biomasses increased more rapidly than those of other groups while that of ciliates slightly decreased. The HETE:AUTO (biomass ratio of heterotroph to autotroph organisms) decreased with temperature, it was < 1 in summer and > 1 in other seasons. Cluster analyses distinguished Inside Bay and Outside Bay on the basis of hydrological characteristics. Consistently, the two subdivisions of Sanggou Bay exhibited different MFW structures as well as distinct tintinnid communities. The main MFW structure difference between Inside and Outside Bay was the biomass ratios of AUTO components to HP. Our results showed that the variations of autotrophic component biomass ratios relative to HP were the main factor responsible for the MFW structure seasonal variation. The spatial difference in MFW structure as well as in tintinnid taxonomic composition between Inside and Outside Bay was linked to the semienclosed nature of the Bay that does not favour efficient mixing with outside Yellow Sea waters.